Inter-limb asymmetry in postural control: Role of individual and contextual factors - Muehlbauer, Thomas; Borgmann, Katharina; Limpach, Sam; Krombholz, Dirk; Panzer, Stefan (Sports Medicine International Open, 2025)
Little is known about how individual and contextual factors affect inter-limb differences in balance performance. Thus, we investigated how these factors influence inter-limb asymmetry in balance. Sixty-four soccer players with diverging levels of training experience (i. e., 2–5 or 6–9 years), 73 swimmers, and 60 age-matched non-athletes performed balance tests with different task specificity (i. e., ecological vs. non-ecological). The magnitude of inter-limb differences was quantified by calculating the limb symmetry index (LSI). Inter-limb performance differences were significantly (p=0.012) lower in athletes with (i. e., soccer players) than without (i. e., swimmers) the preferential use of one leg for postural control. However, differences between limbs did not significantly differ among players with diverging levels of training experience. Further, the observed inter-limb differences in soccer players emerged during ecological test conditions only. Our results suggest that the predominant use of one limb compared to the other for balance requirements does not necessarily lead to a large magnitude of inter-limb asymmetry in soccer players and is also not significantly influenced by the level of training experience. However, from a practitioners’ perspective, ecological as opposed to non-ecological test conditions seem to be more suitable for detecting inter-limb asymmetry in soccer players.
Keywords: balance; inter-limb difference; side-to-side difference; athletes; task Specificity